Statistical Insight into CVD Risk Prevalence Among the Cardiac Patients in Jharkhand, India - Anand, Anushil; Kumar, Prakash; Lenka, Pritam; Ghosh, Sajalendu (Indian Journal of Pharmacy Practice)
Background: Cardiovascular Disease (CVD) is the leading cause of mortality and disability globally and is also very much a significant burden in India. This study aimed to identify prevalent risk factors among hospitalized CVD patients at the Rajendra Institute of Medical Science (RIMS) in Ranchi in the year 2023. Materials and Methods: Utilizing the WHO’s STEP-wise approach; we assessed 516 RIMS patients aged 18 to 69 years with complaints of chest discomfort and breathing difficulties. Results: 4 times more male CVD patients were found than females in the total population. Female patients were mostly above 45 years of age indicating the involvement of menopause. Results revealed a high prevalence of dyslipidemia: 85.66% of patients exhibited abnormal High-Density Lipoprotein (HDL) levels, while 71.7% had an elevated Cholesterol Ratio (CR). Obesity (63.76%) and abnormal Mean Arterial Pressure (MAP) (32.75%) were also notable. Females showed significantly lower HDL levels (96%) compared to males (82%), while males had a higher prevalence of elevated Low-Density Lipoprotein (LDL) levels (56.1% vs. 52.9%). Conclusion: Though Dyslipidemia has been the major contributor to CVD in Jharkhand, metabolic syndrome was present only in 10.27% of patients. Odds ratio analysis indicated males were 1.86 times more likely to be obese than females. Most of the female patients were of postmenopausal age, though their frequency of occurrence was 4 times less than male patients. These findings highlight the main cause of CVD in the Jharkhand population that needs to be intervened from every level possible.
Keywords: Cardiovascular Disease (CVD); Dyslipidemia; Epidemiology; Obesity; Risk Factors